Severe acute pancreatitis: surgical indications and treatment - Heckler, Max; Hackert, Thilo; Hu, Kai; Halloran, Cristopher M.; Büchler, Markus W.; Neoptolemos, John P. (Langenbeck's archives of surgery, 2021)
Acute pancreatitis (AP) is defined as an acute inflammatory attack of the pancreas of sudden onset. Around 25% of patients have either moderately severe or severe disease with a mortality rate of 15-20%.
Published: 10 September 2020
Gesehen am 18.11.2021